Pengaruh Segmentasi Pasar dan Harga Penetrasi terhadap Proses Keputusan Pembelian di Evo 69 Garut - Andri M Nuroni (Jurnal Wacana Ekonomi, 2016)
The existence of steam washing which is currently everywhere with various advantages and prices given makes consumers free to choose according to their wishes. Therefore, to overcome this, the role of management in the company will be very reliable, the success of a company can only be achieved with good management, namely management that is able to maintain company continuity by obtaining maximum profit and consumer sustainability. The purpose of this study is to determine how the influence of market segmentation on purchasing decisions in EVO 69. Also to find out how the effect of price penetration on purchasing decisions in EVO 69. The method used in this study is descriptive and associative methods, with the number of respondents as many as 96 was obtained using the formula for calculating unknown populations, the data analysis technique used multiple linear regression using Microsoft Excel 2013 and SPSS 20. The results showed that there was an effect of market segmentation on consumer purchasing decisions in Evo 69 Garut and there was an effect of price penetration on consumer purchasing decisions. at Evo 69 Garut.